Penerapan Peta Kendali T2 Hotelling dan Generalized Variance Pada Pengendalian Kualitas Produksi Air Mineral Kemasan di PT. Davincy Airindo - Thalib, Karmila; Nurwan; Payu, Muhammad Rezky Friesta (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
One of the companies engaged in the production of drinking water in Gorontalo Province is PT. Davincy Airindo. Established in 2013, the company produces mineral water under the brands Boneva and Es Kristal. The study aims to examine the application of Hotelling’s T2 control chart and the Generalized Variance control chart in monitoring the quality control of bottled mineral water production at PT. Davincy Airindo. Based on the analysis results, it can be concluded that using the Generalized Variance control chart indicates the presence of out-of-control observations, suggesting that the process is not yet stable. Therefore, corrective actions are required to eliminate such observations so that both the Generalized Variance and Hotelling’s T2 control charts indicate a stable process. However, the process capability value is less than 1, indicating that the process is not capable of meeting the specified requirements